Pachydermoperiostosis And An Eyelid Ptosis Associated With Spiky Keratoderma – An Unusual Presentation - S Das; S Chakraborty; NS Sarkar (Nepal Journal of Dermatology, Venereology & Leprology)
Pachydermoperiostosis, ( PDP), a rare hereditary disorder that is characterized by digital clubbing, pachydermia, subperiosteal new bone formation, associated with pain, polyarthritis, cutis verticis gyrata, seborrhoea and hyperhidrosis.  It mainly presents due to disfiguring facial features, widening of the limbs and bone and joint pain. It affects male population predominantly and transmitted as an autosomal dominant trait. There are many constant features associated with it as well as rarer features. Increased proliferation of the fibroblast and dysregulation of matrix protein play a central role in the pathogenesis of the disease.  They are diagnosed primarily on clinical and radiological grounds. Histopathology plays a supportive role in the diagnosis. Such a case has to be differentiated from several other conditions like acromegaly, neurofibroma,,myxedema, primary systemic amyloidosis as wel as from other causes of digital clubbing.